THE ROLE OF PARENTS, FACILITIES AND INFRASTRUCTURE WITH THE BEHAVIOR OF HAND WASHING WITH SOAP IN PRIMARY SCHOOL PUPILS - Nasution, Andreanda; Jayanti, Resty; Anggraini, Sevrima; Andriansyah, Annisaa Perdana; Rahmah, Syifaur (Jurnal Kesehatan Manarang, 2024)
Deaths from diarrheal diseases can be reduced by up to 50%. Washing your hands with soap, if done correctly, can prevent diseases such as diarrhea and ARI. The aim was to determine the relationship between the role of parents, facilities and infrastructure with hand washing behavior among students in grades 3-6 at MI Al-Asyirotussyafi'iyah Kebayoran Lama, South Jakarta. This research is a quantitative research with a cross sectional research design. Quantitative research is research that emphasizes numerical data (numbers) processed using statistical methods. The population of this study were students from grades 3-6 at MI Al-Asyirotussyafi'iyah Kebayoran Lama, South Jakarta, totaling 75 people. The sampling technique in this research was total sampling. Primary Data in this research is primary data, namely students in grades 3-6 at MI Al-Asyirotussyafi'iyah Kebayoran Lama, South Jakarta by filling in an online questionnaire via Google Form. Secondary data for this research is obtained from previous research, official journals and others. There is a significant relationship between the role of parents and the behavior of washing hands with soap of students with a value of OR = 7.51, which means that respondents who have a good parental role have the opportunity to behave well regarding washing hands with soap 8.816 times greater than students. / female students with a poor level of parental role. There is a statistically significant relationship between facilities and infrastructure and students' hand washing behavior with soap with a value of OR = 27.1, which means that respondents with good facilities and infrastructure are 27.1 times more likely to behave well regarding washing hands with soap. compared to students with poor facilities and infrastructure.